Drug Screening of Hair by Liquid Chromatography-Tandem Mass Spectrometry - Hegstad, S.; Khiabani, H.Z.; Kristoffersen, L.; Kunøe, N.; Lobmaier, P.P.; Christophersen, A.S. (Journal of analytical toxicology, 2008)
Hair has become an important matrix for drug analysis, complementary to blood and urine as a matrix. A prolonged detection window makes hair analysis suitable for lhe detection of exposure to illegal and medicinal drugs for periods up to 12 months. In the present study, a liquid chromatography-tandem mass spectrometry (LC-MS-MS) method for drug screening in hair was developed and validated. To 20 mg of hair, 0.45 mL of acetonitrile/25 mM formic acid (5:95 v/v) and 50 µL of deuterated internal standards were added, and the sample was incubated in a water bath at 37°C for 18 h. LC separation was achieved with a Zorbax SB-Phenyl column (2.1 × 100 mm, 3.5-µm particle). Mass detection was performed by positive ion mode electrospray LC-MS-MS and included the following drugs/metabolites: nicotine, cotinine, morphine, 6-monoacetylmorphine, codeine, amphetamine, methamphetamine, 3,4-methylenedioxymethamphetamine, cocaine, benzoylecgonine, 7-aminonitrazepam, 7-aminoclonazepam, 7-aminoflunitrazepam, oxazepam, diazepam, alprazolam, zopiclone, zolpidem, carisoprodol, meprobamate, buprenorphine, and methadone. Within- and between-assay relative standard deviations varied from 2.0% to 12% and 2.7% to 15%, respectively. The accuracies were in the range of −24% to 16%, and recoveries ranged from 25% to 100%. The LC-MS-MS method proved to be simple and robust for the determination of drugs in hair. It has been used for authentic samples in our laboratory in the past year.